2022
DOI: 10.1101/2022.04.05.22273480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity of BNT162b2 COVID-19 vaccine in New Zealand adults

Abstract: BackgroundThere is very little known about SARS-CoV-2 vaccine immune responses in New Zealand populations at greatest risk for serious COVID-19 disease.MethodsThis prospective cohort study assessed immunogenicity in BNT162b2 mRNA vaccine recipients in New Zealand without previous COVID-19, with enrichment for Māori, Pacific peoples, older adults ≥ 65 years of age, and those with co-morbidities. Serum samples were analysed at baseline and 28 days after second dose for presence of quantitative anti-S IgG by chem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Nucleocapsid seroprevalence was used as a surrogate marker of previous SARS-CoV-2 infection. There are limitations in relying upon this marker as some individuals may not mount a nucleocapsid antibody response following SARS-CoV-2 infection, particularly if previously vaccinated, and these antibodies have been observed to wane over time [13,[20][21][22]. However, waning of anti-nucleocapsid antibodies is assay dependent, with the Roche total anti-nucleocapsid antibody assay, used in this study, reported to show high sensitivity out to at least 11.5 months post infection [23].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Nucleocapsid seroprevalence was used as a surrogate marker of previous SARS-CoV-2 infection. There are limitations in relying upon this marker as some individuals may not mount a nucleocapsid antibody response following SARS-CoV-2 infection, particularly if previously vaccinated, and these antibodies have been observed to wane over time [13,[20][21][22]. However, waning of anti-nucleocapsid antibodies is assay dependent, with the Roche total anti-nucleocapsid antibody assay, used in this study, reported to show high sensitivity out to at least 11.5 months post infection [23].…”
Section: Discussionmentioning
confidence: 89%
“…Anti-SARS-CoV-2-nucleocapsid specific antibodies (including IgG) Serum samples were analysed at Southern Community Laboratories in Dunedin (New Zealand). The electrochemiluminescence Elecsys® Anti-SARS-CoV-2 immunoassay (Roche Ltd) was used, in accordance with manufacturer instructions, to detect antibodies that recognise SARS-CoV-2 nucleocapsid protein in serum, which indicates prior infection [13]. Participants were tested at baseline (pre vaccination), prior to third dose and 28 days post third vaccine dose.…”
Section: Laboratory Analysismentioning
confidence: 99%
See 3 more Smart Citations